MURAL AS A MEDIUM OF LANGUAGE LEARNING IN PRESCHOOL EDUCATION - Taufiq Akbar; Puji Anto; M Sjafei Andrijanto (Universitas Indraprasta PGRI, 2020)
Abstract: The purpose of this research is to convert murals as a language learning medium for preschool children. The method of research used is qualitative with the technique of literature studies. Researchers use libraries to find data on subjects and research objects. The result of this study was the stage of the mural as a media-teaching medium for preschool children. The mural as a learning medium of preschool children must be able to represent the will of the child itself. Child behavior against murals is a hallmark of the success of message delivery. The illustration style of the preschool child mural must be adjusted to the needs of the child, such as cartoon illustration style. Color selection is also not to be separated from the needs of children, children tend to prefer a striking color. If there is a typeface applied in the mural then consider the use of round and open letters, not sharp corners or rectanglesKeywords: Mural, language learning media, preschool.